Incremental testing of finite state machines. (10th April 2012) - Chaves Pedrosa, Lehilton Lelis; Vieira Moura, Arnaldo
SUMMARY The automatic generation of test suites for systems modelled as finite state machines (FSMs) is an important problem that impacts several critical applications. Known methods that automatically generate tests for FSMs, specially the W‐method and some derivations, strongly assume that the number of system states is small. If the overall number of states in the FSM specification is relatively large, such methods become difficult to use. However, often in practice, a system is defined as a combination of several subsystems, with the latter already independently designed, developed and tested. In this paper, we define the concept of combined FSMs and introduce a new method to test modular compositions of FSMs. This method allows for a new incremental testing strategy that turns the testing of new systems into a much more scalable process. As an example, we present an infinite family of naturally occurring FSM models for which our method produces exponentially more compact test suites than the W‐method. Copyright © 2012 John Wiley & Sons, Ltd.